Thermal Evaluation of Bone Drilling with a One-Drill Protocol - Sihana Rugova; Marcus Abboud (Bioengineering)
This study evaluates the thermal impact of a one-drill protocol for osteotomy preparation in dental implant surgery. Our findings demonstrate a significant reduction in heat generation compared to traditional sequential drilling, suggesting potential benefits for implant osseointegration and patient comfort. Specifically, the one-drill protocol was associated with lower peak temperatures and a reduced duration of elevated temperatures. These findings suggest that the one-drill protocol may contribute to improved implant stability and reduce the risk of thermal-induced bone damage. While further research is needed to confirm these findings in clinical settings, the results of this study provide promising evidence for the potential advantages of the one-drill protocol in dental implant surgery. Additionally, the one-drill protocol may offer simplified surgical workflows and reduced instrument management, potentially leading to improved efficiency and cost-effectiveness in dental implant procedures.